1999
DOI: 10.1016/s1098-7339(99)90139-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal lipophilic opioids as adjuncts to surgical spinal anesthesia

Abstract: The anesthesia-enhancing properties and side-effect profile of lipophilic opioids administered intrathecally suggest significant roles for these agents as adjuncts to spinal anesthesia for obstetric and outpatient procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
0
48
0
5
Order By: Relevance
“…Kuusniemi et al [15 ] reported that different durations of spinal anesthesia were related to different doses of spinal bupivacaine supplemented with 25 µg fentanyl in patients undergoing urology procedures. Hamber et al [17] in a review article found that a dose of 20-30 µg fentanyl as adjunct to spinal anesthesia produces faster block onset time, improved intraoperative analgesia and decrease incidence of intraoperative nausea and vomiting in obstetric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kuusniemi et al [15 ] reported that different durations of spinal anesthesia were related to different doses of spinal bupivacaine supplemented with 25 µg fentanyl in patients undergoing urology procedures. Hamber et al [17] in a review article found that a dose of 20-30 µg fentanyl as adjunct to spinal anesthesia produces faster block onset time, improved intraoperative analgesia and decrease incidence of intraoperative nausea and vomiting in obstetric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal opioids are usually added to local anaesthetics for spinal anaesthesia in order to improve analgesic quality without prolonging motor block. 10,11 We hypothesized that adding an opioid to hyperbaric bupivacaine for spinal anaesthesia would improve anaesthetic quality without leading to additional complications during TEP. The aim of the study was to evaluate the anaesthetic quality of intrathecal administration of bupivacaine alone, compared with bupivacaine plus fentanyl, in patients undergoing TEP under spinal anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…First, low-doses of IT lipophilic opiods such as fentanyl or sufentanil provide rapid and effective analgesia during labour. 1,13 In addition, low doses of ITS (2.5-10 µg) combined with a local anesthetic hasten the onset of block, and improve intraoperative and postoperative analgesia for two to five hours after Cesarean delivery. 1,13 Our second argument to opt for this ITS dosage was based on a study conducted by Lu et al 22 investigating the dose response of ITS (12.5, 25, or 50 µg) in young adult female volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…1,13 In addition, low doses of ITS (2.5-10 µg) combined with a local anesthetic hasten the onset of block, and improve intraoperative and postoperative analgesia for two to five hours after Cesarean delivery. 1,13 Our second argument to opt for this ITS dosage was based on a study conducted by Lu et al 22 investigating the dose response of ITS (12.5, 25, or 50 µg) in young adult female volunteers. The authors observed patients' response to lower extremity pain and concluded that doses larger than 12.5 µg did not improve the speed of onset, magnitude, or duration of analgesia but only produced a dose-related increase in side effects (nausea, vomiting and respiratory depression).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation